Verbal Grammaticalisation Clines in Coptic - Uljas, Sami (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
The present paper studies grammaticalisation of verbs in Coptic. Various (classes of) expressions found in this language can be shown to occupy different sections or ‘points’ on the continuum/cline of evolution of verbs posited in linguistics that extends from lexical items to auxiliaries, affixes, parts of other lexemes, and finally zero (nothing). The mechanisms that ‘push’ verbs along this continuum turn out to be those seen also in other languages, and the same holds for the semantic and morpho-syntactic signals thereof. Besides being of typological interest, this again emphasises the importance and necessity of studying Coptic from a more diachronic perspective.